2008
DOI: 10.1161/circulationaha.107.733675
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Echocardiographic Dyssynchrony Assessment by Tissue Velocity and Strain Imaging in Subjects With or Without Systolic Dysfunction and With or Without Left Bundle-Branch Block

Abstract: Background-Several echocardiographic dyssynchrony indexes have been proposed to identify responders to cardiac resynchronization therapy using tissue velocity and strain. The present study aimed to compare tissue velocity-derived and strain-derived dyssynchrony indexes in patients with or without systolic dysfunction and left bundle-branch block. Methods and Results-Tissue Doppler imaging was performed in 120 subjects divided into 4 groups: group 1 (nϭ40), normal subjects; group 2 (nϭ20), normal left ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
2
4

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 47 publications
7
82
2
4
Order By: Relevance
“…17 However, these attempts were challenged in prospective multicenter studies because of poor reproducibility, low positive predictive values, and poor accuracy even in healthy control subjects. 4-7, 18 Several studies suggested that STE overcame some limitations of tissue velocity imaging and provided a better measurement of mechanical dyssynchrony. The dyssynchrony parameters by STE were proposed as additional indices to predict CRT response in single-center studies or those with small sample sizes.…”
Section: Conventional Dyssynchrony Parameters and Ste Parametersmentioning
confidence: 99%
“…17 However, these attempts were challenged in prospective multicenter studies because of poor reproducibility, low positive predictive values, and poor accuracy even in healthy control subjects. 4-7, 18 Several studies suggested that STE overcame some limitations of tissue velocity imaging and provided a better measurement of mechanical dyssynchrony. The dyssynchrony parameters by STE were proposed as additional indices to predict CRT response in single-center studies or those with small sample sizes.…”
Section: Conventional Dyssynchrony Parameters and Ste Parametersmentioning
confidence: 99%
“…According to American Heart Association Scientific Statement, the heart should be divided into 17 segments for assessment of the myocardium and the left ventricular cavity (10). The time to peak systolic longitudinal strain in (Tssl) of 17 LV segments has been paid much attention as LV systolic synchrony parameter recently (17)(18)(19). As the resting heart rate predicts longevity and cardiovascular diseases, and current evidence suggests that it is also an important marker of outcome in cardiovascular disease, including coronary artery disease (20).…”
Section: Discussionmentioning
confidence: 99%
“…11 Strain measures deformation and therefore contraction and may overcome some of the problems cause by the inability of velocity to distinguish contraction from rocking movements and tethering. Miyazaki et al 11 compared measures of dyssynchrony with tissue velocity imaging (TVI) and strain in 120 subjects (40 normal, 20 LBBB with normal LV, 20 LV dysfunction and no LBBB, and 40 LV dysfunction and LBBB).…”
Section: Articles P 2608 and P 2617mentioning
confidence: 99%